MODERN STATE AND PROGNOSES OF DEVELOPMENT OF UKRAINIAN MARKET OF NANOSIZED POWDERS - Malyshev , Victor; Gab , Angelina; Patsalovskaya , Lyudmila; Vodennikova , Oksana; Sergienko , Tatiana; Vodennikova , Larisa (Scientific Journal "Metallurgy", 2020)
The Ukrainian market of nanosized powder materials is reviewed and the main directions for the modification of nanopowders: nanocomposites, nanotubes, fullerenes, nanoparticles, nanomembranes, and others are determined. Systematization of literary data in relation to description of modern Ukrainian industry of nanotechnologies on the most essential indexes and progress trends showed that the Ukrainian market of nanotechnologies was on the initial stage of becoming. The main directions of research and development work in the field of nanotechnology are analyzed such as the production of nanomaterials, their use in nanoscale devices and nanotools. The structure of the potential volume of the Ukrainian market of nanopowders has been determined: in the electronics enterprises (for use as condenser powders) from 5 to 10 tons per year, in the automotive industry (for the manufacture of catalysts) up to 5 ktons/year and in the enterprises of the military complex (for the manufacture of sensors) from 50 to 250 kg/year. The average cost of nanopowders of metal oxides (zirconium oxide, aluminum oxide, barium titanite, copper oxide and iron oxide) on the Ukrainian market of powder materials is given. The main participants in the Ukrainian market of nanomaterials are identified, namely PJSC "Dneprospetsstal" and PJSC "Kremenets Powder Metallurgy Plant". The main potential consumers of nanopowders in Ukraine are considered: metallurgy, electronics, energy, engineering, transport industry, aerospace industry. The main stimulating factor of the lag of the Ukrainian electronic products industry from foreign countries is identified as the unpreparedness of Ukrainian manufacturers to compete with imported products in the ratio of price to quality, the inability to function in a market economy, and the low efficiency of public-private partnerships. The forecasts of nanopowder production (nickel nanopowders, yttrium oxide nanopowders, cerium nanopowders, silicon dioxide nanopowders, titanium nanopowders) from 2020 to 2025 are considered and the most promising types of them are determined.